Formulation of Herbal Soap against Acne Causing Bacteria - Attaullah, Anjum; Govindarajulu, Aruna; K, Mohana Priya; KF, Mubeena; R, Sreenithi; Rafiq, Summera; Shahina, Shaik Jasmine (Asian Journal of Biological and Life Sciences)
The use of herbs on skin disorders has been done for thousands of years. Herbal remedies, including those for many kind of disorder especially skin disorders, are currently gaining popularity among patients. In Asia, especially in south east Asian countries, herbal treatments that have been used from ages are now being studied scientifically. In India, records of Ayurvedic medicine, a method of medicine with natural roots date back to about 3000 BC. The system of Ayurvedic medicine combines physiological and holistic principles. Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus in the follicular canal and sebum production are the reason for leading to Acne vulgaris. Inflammation in acne is caused by Staphylococcus aureus. In the present study, aqueous extract of herbs like Guava leaves, Turmeric, Aloe Vera, Soap nuts and Rose petals were used to formulate a herbal soap to combat acne. The preliminary phytochemical analysis of the aqueous extract of these herbs showed the presence of various secondary metabolites such as saponins, phenols, tannins, terpenoids, glycosides and quinones. In vitro antibacterial activity was performed against Staphylococcus aureus and E. coli using agar well diffusion method. The zone of inhibition with guava leaves was observed to be 17mm, while 11 mm was observed with turmeric for Staphylococcus aureus. While with E. coli, Guava leaves showed a zone size of 9mm and no zones were observed with Turmeric and Aloe vera extracts. Although, Aloe vera is known for its antibacterial activity, in our study Aloe vera did not exhibit any antibacterial activity.
Keywords: Antibacterial activity; Guava leaves; Herbal soaps; S. aureus; Turmeric